Guanidinium-rich lipopeptide functionalized bacteria-absorbing sponge as an effective trap-and-kill system for the elimination of focal bacterial infection. (August 2022) - Li, Feng; Lin, Liming; Chi, Jiaying; Wang, Hui; Du, Minqun; Feng, Disang; Wang, Liqing; Luo, Rui; Chen, Hangping; Quan, Guilan; Cai, Jianfeng; Pan, Xin; et al.
Abstract: Focal bacterial infections are often difficult to treat due to the rapid emergence of antibiotic-resistant bacteria, high risk of relapse, and severe inflammation at local lesions. To address multidrug-resistant skin and soft tissue infections, a bacteria-absorbing sponge was prepared to involve a "trap-and-kill" mechanism. The system describes a guanidinium-rich lipopeptide functionalized lyotropic liquid-crystalline hydrogel with bicontinuous cubic networks. Amphiphilic lipopeptides can be spontaneously anchored to the lipid-water interface, exposing their bacterial targeting sequences to enhance antibacterial trapping/killing activity. Computational simulations supported our structural predictions, and the sponge was confirmed to successfully remove ∼98.8% of the bacteria in the medium. Release and degradation behavior studies indicated that the bacteria-absorbing sponge could degrade, mediate enzyme-responsive lipopeptide release, or generate ∼200 nm lipopeptide nanoparticles with environmental erosion. This implies that the sponge can effectively capture and isolate high concentrations of bacteria at the infected site and then sustainably release antimicrobial lipopeptides into deep tissues for the eradication of residual bacteria. In the animal experiment, we found that the antibacterial performance of the bacterial-absorbing sponge was significant, which demonstrated not only a long-term inhibition effect to disinfect and avoid bacterial rebound, but also a unique advantage to protect tissue from bacterial attack. Statement of significance: Host defense peptides/peptidomimetics (HDPs) have shown potential for the elimination of focal bacterial infections, but the application of their topical formulations suffers from time-consuming preparation processes, indistinctive toxicity reduction effects, and inefficient bacterial capture ability. To explore new avenues for the development of easily prepared, low-toxicity and high-efficiency topical antimicrobials, a guanidinium-rich lipopeptide was encapsulated in a lyotropic liquid-crystalline hydrogel (denoted as "bacteria-absorbing sponge") to achieve complementary superiorities. The superior characteristic of the bacteria-absorbing sponge involves a "trap-and-kill" mechanism, which undergoes not only a long-term inhibition effect to disinfect and avoid bacterial rebound, but also effective bacterial capture and isolating action to confine bacterial diffusion and protect tissues from bacterial attack. Graphical abstract: Image, graphical abstract